SARS-CoV-2 Membrane Protein Inhibits Type I Interferon Production Through Ubiquitin-Mediated Degradation of TBK1 - Sui, Liyan; Zhao, Yinghua; Wang, Wenfang; Wu, Ping; Wang, Zedong; Yu, Yang; Hou, Zhijun; Tan, Guangyun; Liu, Quan (Frontiers in Immunology, 2021)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the causative pathogen of current COVID-19 pandemic, and insufficient production of type I interferon (IFN-I) is associated with the severe forms of the disease. Membrane (M) protein of SARS-CoV-2 has been reported to suppress host IFN-I production, but the underlying mechanism is not completely understood. In this study, SARS-CoV-2 M protein was confirmed to suppress the expression of IFNβ and interferon-stimulated genes induced by RIG-I, MDA5, IKKε, and TBK1, and to inhibit IRF3 phosphorylation caused by TBK1. SARS-CoV-2 M could interact with MDA5, TRAF3, IKKε, and TBK1, and induce TBK1 degradation via K48-linked ubiquitination. The reduced TBK1 further impaired the formation of TRAF3-TANK-TBK1 complex that leads to inhibition of IFN-I production. Our study revealed a novel mechanism of SARS-CoV-2 M for negative regulation of IFN-I production, which would provide deeper insight into the innate immunosuppression and pathogenicity of SARS-CoV-2.